Effectiveness of the intellectual property center program in the inventory and recording of communal intellectual property at BRIDA Gianyar Regency - I Nyoman Mudita (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Communal Intellectual Property (KIK) is an important asset that includes traditional knowledge, cultural expressions, genetic resources, and geographical indications that are passed down from generation to generation in a community. To protect KIK from foreign claims and ensure that economic and cultural benefits continue to be enjoyed by the community of origin, the Indonesian government through the Directorate General of Intellectual Property (DJKI) launched the Intellectual Property Center (Sentra-KI) Program. This program aims to inventory and record KIK as an initial step in legal protection. This study analyzes the effectiveness of the Sentra-KI Program at BRIDA Gianyar Regency in supporting KIK recording, and identifies factors that influence its success. The results of the study show that although this program has increased public awareness and provided a better recording system, there are still various obstacles, such as limited human resources, lack of public understanding, bureaucratic obstacles, and suboptimal digital infrastructure. To overcome these challenges, a more comprehensive strategy is needed, including improving education, digitizing services, strengthening partnerships with related institutions, optimizing budgets, and simplifying administrative procedures. By implementing effective strategies, the Sentra-KI Program is expected to improve the protection and sustainable use of KIK in Gianyar Regency.